Exposing effect of comb-type cathode electrode on the performance of sediment microbial fuel cells - Wang, Chin Tsan; Lee, Yao Cheng; Ou, Yun Ting; Yang, Yung Chin; Chong, Wen Tong; Sangeetha, Thangavel; Yan, Wei Mon (Elsevier, 2017)
Sediment microbial fuel cells (SMFCs) are an innovative, green technology with great potential, and they utilize a voltage drop of redox potential between aerobes and anaerobes to produce electricity and degrade organic wastewater. However, the power performance and degradation rate in SMFCs are limited by the low concentration of dissolved oxygen on the cathode. Therefore, in this study, SMFCs with comb-type cathode electrodes with carbon cloths exposed partly to air and embedded partly in the reactor substrate were designed and operated. They were utilized for enhancing the power density and the effect of three different exposed areas of cathode electrode for improving transfer of oxygen. Results showed that the power density reached 3.77 × 10−2 mW/m2 for 75% of the (MA75) exposed area, which was 1.93 times than that of 50% of the (MA50) exposed area and 6.44 times than that of 0% (i.e., completely immersed; MA0) exposed area. These results indicated that the exposed area of the cathode electrode had a positive effect on the power performance of SMFCs and would reduce the impedance of the cathode. These findings would apparently offer useful information on the feasibility of SMFCs for wastewater treatment applications in the future.